ESTIMATION OF THICKNESS AND VOLUME OF THE BARK AND ITS RELATIONSHIP WITH THE DIAMETER AND THE HEIGHT OF Populus nigra L TREES GROWN IN STANDS AT THE NORTHERN OF IRAQ - Mohammed Asim Saeed Al-Ali (Mesopotamia Journal of Agriculture)
The study was carried out in Dohok in the north of Iraq, exactly in Zakho region, Where Populus nigra stands are widely spread within irrigated stands that are depending on feshkhabour river. Study area involved (45) samples which are randomly selected regions that represents state of the stands. Each sample was (0.1) hectare area, from these plots eighty six reading were recorded for the diameter over and under the bark taken from different height level for 13 standard trees that represent all ages, densities, and diameters for these stands. Data were inserted in linear and non linear regression program, to determine bark factor (K), which found to be (0.95). The volume of the bark was calculated by taking (30) standard trees that represent all ages and densities. Tree volume over and under the bark and difference between them were calculated. Several mathematical equations were found that represent the relation between bark volume as a depended variable, and the diameter at d.b.h. and total height as an in depended variables. From these equations, bark volume was estimated depending on these easy in depended variables. Also we be able to found a mathematical equation to estimate bark thickness from diameter.